Allergic Contact Dermatitis and Autoeczematization to Proctosedyl® Cream and Proctomyxin® Cream - J.D. Matthew Hughes; Melanie D. Pratt (Karger Publishers, 2018)
Proctosedyl® and Proctomyxin® are two commonly prescribed hemorrhoid therapies. Their topical application to the perianal region may be complicated by a local allergic contact dermatitis and subsequent autoeczematization reaction. We present three cases of an autoeczematization (ID) reaction to varying topical allergens found in Proctosedyl®/Proctomyxin®. It is our recommendation that physician and patient education, avoidance of allergens (or cross-reactants), and appropriate choice of topical corticosteroid is important in preventing and avoiding flares.